Economic uncertainty and tourism consumption. Issue 4 (June 2022) - Nguyen, Canh Phuc; Thanh, Su Dinh; Nguyen, Bach
This study examines the influence of economic uncertainty on tourism. The key hypothesis to test is that while economic uncertainty reduces outbound tourism, it may boost domestic tourism due to the economic-stagnant effects. Utilizing the framework of the theory of reasoned action to analyze a global sample of 124 countries over the period 1996–2017, we find some initial evidence showing that an increase in economic uncertainty encourages domestic tourism while reducing outbound tourism in the global sample. Notably, while these effects are consistent in the upper-middle-income economies, an increase in uncertainty has a positive impact on both domestic and outbound tourism in lower-middle-income economies and a negative impact on both domestic and outbound tourism in higher-income economies. The key implementation of this study is that tourism development is not always associated with economic development and stability; sometimes it could be a signal of economic stagnancy and inactiveness.